PENGGUNAAN MEDIA SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V-B SDN MANUKAN KULON II/499 SURABAYA - Kholisatun Nabila; Ulhaq Zuhdi; Wandik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This classroom action research was conducted based on the problems found at SDN Manukan Kulon II/499 Surabaya Surabaya. The issue is in the lack of enthusiasm among students towards studying the content of emulating Pancasila conduct, which therefore affects their inferior academic performance. The research aims to enhance student learning outcomes by utilizing Smart Box media to simulate Pancasila behavior in grade V. The study included a sample of 27 kids from fourth to sixth grade at SDN Manukan Kulon II/499 Surabaya. Objective of this study is to examine student learning results. Primary methods of data collecting are observation, testing, and documenting. The study was carried out in two cycle. In cycle I, the highest score obtained was 100 and the lowest was 40, with a class average of 71.5. Students who achieved learning completion were 31%, and students who had not achieved learning completion were 69%. In cycle II, the highest score obtained was 100 and the lowest was 70, with a class average of 88.8. Students who achieved learning completion were 77%, and those who had not achieved learning completion were 23%. Therefore, it can be inferred that the consumption of Smart Box media has the potential to enhance the educational achievements of students in classes V-B at SDN Manukan Kulon II/499 Surabaya on the material of imitating Pancasila behavior in the Pancasila Education subject.